Engineering Cell‐Compatible Paper Chips for Cell Culturing, Drug Screening, and Mass Spectrometric Sensing. Issue 15 (17th September 2015) - Chen, Qiushui; He, Ziyi; Liu, Wu; Lin, Xuexia; Wu, Jing; Li, Haifang; Lin, Jin‐Ming
Abstract : Paper‐supported cell culture is an unprecedented development for advanced bioassays. This study reports a strategy for in vitro engineering of cell‐compatible paper chips that allow for adherent cell culture, quantitative assessment of drug efficiency, and label‐free sensing of intracellular molecules via paper spray mass spectrometry. The polycarbonate paper is employed as an excellent alternative bioscaffold for cell distribution, adhesion, and growth, as well as allowing for fluorescence imaging without light scattering. The cell‐cultured paper chips are thus amenable to fabricate 3D tissue construction and cocultures by flexible deformation, stacks and assembly by layers of cells. As a result, the successful development of cell‐compatible paper chips subsequently offers a uniquely flexible approach for in situ sensing of live cell components by paper spray mass spectrometry, allowing profiling the cellular lipids and quantitative measurement of drug metabolism with minimum sample pretreatment. Consequently, the developed paper chips for adherent cell culture are inexpensive for one‐time use, compatible with high throughputs, and amenable to label‐free and rapid analysis. Abstract : The paper describes a strategy for in vitro engineering of cell‐compatible paper chips that allows for adherent cell culture onto the polycarbonate scaffolds and facilitates the optical imaging. Therefore, an approach of in situ sensing of the cellular components from adherent cells by paper spray mass spectrometry is developed.